Regional Workshop on Cassava Breeding and Agronomy Research in Asia (1987, Rayong, Thailand). Cassava breeding and agronomy research in Asia: Proceedings of a regional workshop - Howeler, Reinhardt H.; Kawano, K (International Center for Tropical Agriculture, 1988)
In Rayong, Thailand, a regional workshop was carried out with breeders and agronomists of the various cassava producing countries in southern Asia in an attempt to establish a cassava research network to increase cassava productivity in the region and improve the prevailing standard of living. Advances in the development of new and higher yielding var. and of improved cultural practices were discussed. Individual papers presented at this workshop are recorded in this publication under the following consecutive no.: 0236 0239 0242 0248 0257 0258 0259 0268 0272 0326 0333 0339 0341 0343 0344 0349 0350 0351 0353 0471 0473 0521. (CIAT)